Relasi Dispersi dalam Pandu Gelombang Planar Nonlinear Kerr - Hengki Tasman; Edy Soewono (Indonesian Journal of Physics, 2002)
In this paper planar waveguides with Kerr-type nonlinearity are considered. By using an effective refractive index method and averaging, an implicit dispersion relation is obtained analitically for the waveguides. This dispersion relation can simplify numerical calculation in obtaining dispersion curves. Dispersion relation curves with different averaging schemes for symmetric planar waveguides are shown here.